Культурно-хронологическая интерпретация Северского городища близ с. Меловая на Донце - Колода, В. В. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary V. Koloda. Cultural and Chronological Interpretation of the Northern Billfort at Melovaya Village by the Donets River There is a hillfort with soil banks at the territory of the modern hamlet at a distance of 4 kilometres to the northern-western part of Melovaya village. On the basis of archaeological serveying in the middle of XX century this hillfort put into archaeological use as a monument of Scythoid population of the Dniepre Left-side forest-steppe. It is registered to the defensive outpost function of settled farmer population in the Early Iron Age (IV BC) in the Severskiy Donets basin for nomad attack. Archaeological excavations that were made in the end of the last century showed that there was no hillfort of Scythian epoch and it lets us belong it to the Early Middle Ages — Saltov archaeological culture (the mid. VIII–the mid. X A.D). This hillfort was the centre of a small household micro region and was a connectinglink between densely populated forest-steppe region of the northern-western Khazaria and steppe monuments of the middle stream of the Severskiy Donets.